Implementation of Practicum Method as a Strategy to Strengthen Science Process Skills at Secondary School Level - Jannah, Rikhatul; Wulandari, Ria (SEJ (Science Education Journal), 2025)
Science process skills are an important aspect in science learning and play a role in training students' scientific thinking skills. However, facts in the field show that students still have difficulties in making systematic observations, formulating hypotheses, designing and conducting experiments, and interpreting data appropriately. This condition is exacerbated by the lack of practicum activities that can train science process skills. The purpose of this study was to describe the implementation of the practicum method on the science process skills of junior high school students. This type of research is a quasi-experiment with a non-equivalent control group research design. The study population was 115 students and the sample was 46 students. The sampling technique used random sampling which was grouped into control and experimental classes. The data analysis technique used N-gain and Mann Whitney test. The results showed that there was no increase in science process skills in the control and experimental classes. In addition, there was no significant difference between the science process skills of the control and experimental classes. It can be concluded that the practicum method in this study did not have an impact on students' science process skills.